Experience of Dental Caries of Adult Patients in Relation To The Characteristic of Dental Visit and Brushing Behavior In Tikrit City (Mustansiria Dental Journal, 2018)
Aim: Dental decay is a process in which the hard mineral structure of teeth isdissolved. The process produces a cavity on the crown of the tooth or a softeningof the root surface. Without regular dental care people are often unaware of thecondition, whereas those who usually seek dental care for a check-up are morelikely to have dental decay treated in a timely manner The aim of the presentstudy was to determine the caries experience of public dental patients by age, sexwith the type of dental visit and brushing behavior in adults in Tikrit city, Iraq.Subjects and methods: A sample of 1284 individuals(580 males and 704females)with an age range of (18-60 years) attending the teaching dental hospitalof collage of dentistry of Tikrit university and the specialized dental center , wereexamined according to WHO guidelines using DMFT index. Questionnaires wereused to assess the level of dental health attitude among the individuals.Results: The distribution of patients was high at younger age for both sexes.Emergency visit had a higher percentage of patients (82.2%). 63.6% of thepatients brush their teeth two or more. The mean DMFT scores were 7.5 (8.3 forfemale and 6.7 for male). Mean DMFT for both sex increases with age. Thepercentage of decayed teeth (D/DMFT%) was the highest among younger agegroup (60.7% for female and 63.1% for male). There was statistically a highlysignificant difference between age, sex, dental visit type and brushing behaviorand DMFT. Emergency patient did show higher level of decayed and missingteeth while general patient did show higher level of filled teeth. Emergencydental visit had higher percentage of decayed teeth (57.3%) than general dentalvisit (42.5%). One or less brushing patient had higher level of decayed andmissing teeth, while two or more brushing patient show higher level of filledteeth. The percentage of decayed teeth for one or less brushing patients was(62.9%) higher than two or more brushing patients (50.1%).Conclusion: It was concluded that the present study findings for DMFT scores washigher than the global standers according to the world health organization(WHO). Therefore, there is a great need to combine restorative-oriented dentalservices with preventive- oriented dental services in order to improve the oralhealth status of this population.